The association of USMLE Step 1 and Step 2 CK scores with residency match specialty and location - Gauer, Jacqueline L. (Med Educ Online, 2017)
Background: For future physicians, residency programs offer necessary extended training in specific medical specialties. Medical schools benefit from an understanding of factors that lead their students to match into certain residency specialties. One such factor, often used during the residency application process, is scores on the USA Medical Licensing Exam (USMLE). Objectives: To determine the relationship between USMLE Step 1 and Step 2 Clinical Knowledge (CK) scores and students’ residency specialty match, and the association between both USMLE scores and state of legal residency (Minnesota) at the time of admission with students staying in-state or leaving the state for residency program. Design: USMLE scores and residency match data were analyzed from five graduating classes of students at the University of Minnesota Medical School (N = 1054). Results: A MANOVA found significant differences (p < 0.001) between residency specialties and both USMLE Step 1 and Step 2 CK scores, as well as the combination of the two. Students who matched in Dermatology had the highest mean USMLE scores overall, while students who matched in Family Medicine had the lowest mean scores. Students who went out of state for residency had significantly higher Step 1 scores (p = 0.027) than students who stayed in-state for residency, while there was no significant difference between the groups for Step 2 scores. A significant positive association was found between a student who applied as a legal resident of Minnesota and whether the student stayed in Minnesota for their residency program. Conclusions: Residency specialty match was significantly associated with USMLE Step 1 and USMLE Step 2 CK scores, as was staying in-state or leaving the state for residency. Students who were legal residents of the state at the time of application were more likely to stay in-state for residency, regardless of USMLE score. Abbreviations: CK: Clinical knowledge; COMLEX: Comprehensive Osteopathic Medical Licensing Examination; GME: Graduate medical education; NRMP: National Resident Matching Program; UME: Undergraduate medical education; USMLE: United States Medical Licensing Examination